Trying-out Digital Technologies in Trying Times: A Collection of Observations From a Collegial Adventure During Covid-19 - Hooper, P; Anderson, T; Nates, R; Moir, T; Beckerleg, M; Protheroe, M; Whittington, C; Hadrup, M (Australasian Association for Engineering Education (AAEE), 2020)
CONTEXT In recent decades there has been significant discussion in the popular press about digital technologies enabling society to transition to a working-from-home scenario. Similarly, literature in the engineering education space has extolled the possibilities and potential for online education, digital technology, asynchronous, poly-synchronous, remote and flipped classroom learning. However, what is less well known are the strategies that academics use to cope with these technologies, as few studies explore the academic “voice”. PURPOSE OR GOAL The concept of the “modern” student being a “digital native” has, rightly or wrongly, been widely presented as a truth of education in the 21st century. This “truth” rests heavily on the assumption that students have lived in an age of personal computing and thus will have (somehow) developed the skills to work in “virtual” spaces. Of course, this may be interpreted as taking a rather cynical view, although it does open us to the consideration of how students acquire these skills. Furthermore, if there is the expectation that students have the skills to cope with on-line education, how do we equip academic staff to also meet this expectation? APPROACH OR METHODOLOGY/METHODS Many universities offer some form of orientation or training in the use of electronic tools or learning management systems, however anecdotal evidence would suggest that these are not always highly regarded by academic staff. With the rapid transition to online education precipitated by the Covid-19 pandemic, the need for academic staff to at least be conversant, and ideally be proficient, in the use of online education tools reached a crescendo. This work presents a collection of narratives from a group of academics who early in the transition grouped together, outside any formal institutional structure, in a journey of (online) educational discovery. It examines the concept of the academic as student and the value of peer-to-peer instruction in developing the skills to facilitate online education. ACTUAL OR ANTICIPATED OUTCOMES Through the use of personal narratives, this work highlights the value that the, perhaps antiquated, notion of collegiality can still bring to professional development. It also demonstrates that academics, given autonomy, can collaborate in educational endeavours to deliver outcomes beyond what typical institutional structures might deliver. CONCLUSIONS/RECOMMENDATIONS/SUMMARY This work highlights the value of peer-based mentoring for academics new to online education. It also acknowledges that the success of the strategy lay in fostering a “safe space” for professional development. Moreover, it delivers an alternative perspective to formal Learning and Teaching structures within universities, suggesting that these could be improved by allowing academics to “run wild” (within a safe space) while exploring technology.
Keywords: Academic voice; Online education; Professional development; Distance learning; Collegiality